A comparative study of the glucose challenge test, fasting blood glucose test, and post-prandial blood glucose screening to identify gestational diabetes mellitus - Sravanthi Pandala; Shivani D; Naga Jyothi Gunturu (Golestan University Of Medical Sciences, 2024)
Background: There is currently a scarcity of population-based records related to the prevalence of gestational diabetes mellitus (GDM) in India. There were various recommendations for screening and diagnostic tests for GDM, and no uniform standard has yet been established. Hence, a comparative study was conducted to assess the usefulness of the glucose challenge test (GCT) and fasting blood glucose (FBG)/post-prandial blood glucose (PPBG) test for the screening of GDM in pregnant women attending the prenatal clinic outpatient department. Methods: This is a comparative observational study involving 300 apparently normal pregnant who were randomly allocated to GCT and FBG/PPBG cohorts of 150 each. The tests were performed at 4 intervals: 8 to 10 weeks, 16 to 20 weeks, 24 to 28 weeks, and 32 to 36 weeks. All diagnosed GDM cases were appropriately handled. Results: Gestational diabetes mellitus was seen in 2.67% of the FBG/PPBG cohort and 5.34% of the GCT cohort. The GCT test identified 25% of GDM subjects before 24 weeks of gestation, 50% in 24 and 28 weeks, and 25% in > 32 weeks of gestation. The highest prevalence of GDM was noted in the 26-30-year age group. The highest prevalence of GDM was noted in pregnant women with ≥ 26 kg/m2 of body mass index (BMI), with 75% in the FBG/PPBG group and 62.5% in the GCT group. The incidence of GDM was higher in primigravida, 75% in the FBG/PPBG group, and 50% in the GCT group. A higher prevalence was observed in pregnant women of class 4 of socioeconomic status, and it was 75% in the FBG/PPBG group and 75% in the GCT group. A higher prevalence was noted in those with higher secondary education. The majority of GDM cases gave birth at term by labor, and there were no assisted vaginal births in this group. Moreover, 75% of GDM cases in the FBG/PPBG cohort and 62.5% of GDM cases in the GCT cohort had Caesarean section. Besides, 50% of infants from GDM mothers in the FBG/PPBG cohort were hospitalized, while 12.75% were admitted in the GCT cohort. The birth weight of neonates from GDM mothers was 3.09 ± 0.5 kg, 3.11 ± 0.6 kg in normal mothers, 2.98 ± 0.6 kg in the FBG/PPBG cohort, and 2.9 ± 0.5 kg in the GCT cohort. Conclusion: Irrespective of the last meal, the GCT in all pregnant women is an effective and easy screening approach for 1-step screening for the early diagnosis of GDM for subsequent management at the early gestational pregnancy, which can minimize the adverse obstetric and perinatal outcomes.